Current status and potential of bacteriocin-producing lactic acid bacteria applied in the food industry - Qingping Liang; Wei Zhou; Siyuan Peng; Ziyu Liang; Zhemin Liu; Changliang Zhu; Haijin Mou (Current Research in Food Science)
Lactic acid bacteria (LAB) have been widely applied in the food industry and have brought many beneficial effects on food products, and some of those benefits are related to their metabolic product. Bacteriocins produced by LAB have attracted the attentions for application in the food industry as natural food bio-preservatives because of their antimicrobial activity against the food spoilage and pathogenic bacteria. With the increasing demands of consumers for more healthier food and investigations on natural food preservatives, the bioactivity of bacteriocins allows them to give the application values to the bacteriocin-producing LAB. Accordingly, the capacity of LAB to produce bacteriocin in the aspects of classifications, mode of action, biosynthesis mechanisms are introduced, which leads to further consideration of the current status and potential values of bacteriocin-producing LAB applied in the food industry. The comparation of guidelines of LAB and bacteriocins for food application are also proposed for better understanding their practical application promising. This review will be helpful for current and future researches on the application of bacteriocin-producing LAB in the food industry.